Two-step Structural Break-down of Mesophase Pitch in Large Amplitude Oscillatory Shear - Choi, Jiho; Chae, Yangki; Kim, Sung-Soo; Tae-Hwan, Kim; Lee, Sung Ho (2023 한국탄소학회 춘계학술대회, 2023)
Pitch is a major precursor material for manufacturing carbon fibers. To obtain high-performance pitch-derived carbon fibers, mesophase pitch has been frequently adopted because it has a higher degree of ordered arrangement along the fiber axis than isotropic pitch during the spinning process. Mesophase refers to the optically anisotropic intermediate phase of graphitizable carbon. Polyaromatic mesogens, which are constituent molecules of mesophase pitch, play a key role in enhancing the orientation to the fiber axis. Mesogen units in mesophase pitch exhibit a discotic liquid crystalline nature; therefore, mesophase pitch-derived fibers entail microdomains that can evolve into turbostratic carbon structures with further heat treatment. Owing to the high degree of graphitizability and axial preferred orientation, mesophase pitch-based carbon fibers show a markedly high tensile modulus, which is directly linked to their superior thermal and electrical conductivities. Insight regarding rheological behavior of molten mesophase pitch plays a key role in design of melt spinning process. Most of studies in literature have focused on steady shear deformation, and so lack deeper understanding of viscoelastic properties of mesophase pitch. Here, we perform oscillatory tests which allow for a simple conceptual separation of elastic and viscous contributions. Since it is inevitable to apply nonlinear deformation to mesophase pitch during spinning process, it is required to understand viscoelasticity of mesophase pitch under large amplitude oscillatory shear (LAOS) deformation. Interestingly, mesophase pitch shows two slopes in nonlinear regime of strain amplitude sweep. We analyze waveforms in linear regime and two different LAOS regimes by using sequence of physical processes (SPP) method. SPP framework enables us to calculate time-dependent viscoelastic metrics under LAOS deformation based on the FrenetSeeret apparatus in three dimensional deformation space and provide clear physical interpretation for a curve in ColeCole plot. Mesophase pitch in first LAOS regime experience complicated rheological behaviors such as reformation/yielding and backflow, while the molten pitch transformed into typical viscoelastic liquid in second LAOS regime. By using small angle X-ray scattering, we link those sequential behaviors during an oscillation with the liquid crystalline nature of mesogens. Under the deformation in first LAOS regime liquid crystalline domains in the pitch is deformed and flows like a single particle. Partial break-down of liquid crystalline domain occurs in second LAOS regime. These insights regarding structure-property relationship for transient nonlinear rheology of mesophase pitch will help in designing a better spinning process by enhancing the orientation of liquid crystalline domains.